2000
DOI: 10.1046/j.1365-2125.2000.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific binding of drugs to human liver microsomes

Abstract: Aims To characterize the nonspeci®c binding to human liver microsomes of drugs with varying physicochemical characteristics, and to develop a model for the effect of nonspeci®c binding on the in vitro kinetics of drug metabolism enzymes. Methods The extent of nonspeci®c binding to human liver microsomes of the acidic drugs caffeine, naproxen, tolbutamide and phenytoin, and of the basic drugs amiodarone, amitriptyline and nortriptyline was investigated. These drugs were chosen for study on the basis of their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 23 publications
7
118
0
Order By: Relevance
“…Thus, plasma methadone concentration is less important in determining inhibition of morphine clearance compared with competitive inhibition. The apparent K i values reported here may also be an overestimation of actual K i values due to possible nonspecific binding of methadone to the microsomes, as is common for other basic amine drugs [48]. Also, in vivo methadone concentrations in the liver are likely to be larger than plasma concentrations, as …”
mentioning
confidence: 68%
“…Thus, plasma methadone concentration is less important in determining inhibition of morphine clearance compared with competitive inhibition. The apparent K i values reported here may also be an overestimation of actual K i values due to possible nonspecific binding of methadone to the microsomes, as is common for other basic amine drugs [48]. Also, in vivo methadone concentrations in the liver are likely to be larger than plasma concentrations, as …”
mentioning
confidence: 68%
“…Based on these assumptions, extrapolated whole organ CL int values are 167.8, 7.9 and 4.4 l h x1 for liver, kidney and small bowel, respectively. Correction of kinetic data is necessary where nonspeci®c microsomal binding occurs [5], and hence the nonspeci®c binding of MPA to hepatic microsomes was determined. Ratios of MPA concentrations in the buffer and microsomal compartments of the equilibrium dialysis apparatus were 1.02 : 1, …”
Section: Resultsmentioning
confidence: 99%
“…Non-speci®c microsomal binding of MPA Non-speci®c binding of MPA to human liver microsomes was investigated by equilibrium dialysis, according to the procedure of McLure et al [5]. One compartment of the dialysis apparatus contained MPA (50, 250 or 1000 mM), human liver microsomes (0.05 mg ml x1 ; pooled microsomes from the ®ve livers used previously) and phosphate buffer (0.1 M, pH 7.4), and the other compartment phosphate buffer alone.…”
Section: Microsomal Incubations and Measurement Of Mpag Formationmentioning
confidence: 99%
“…As a result, the decrease in reaction rates would be expected to be proportional to the extent of protein binding at substrate concentrations below K m . In addition, the apparent K m determined on the basis of the added concentration would then be higher than the "true" K m , but the V max should not be affected, as predicted by McLure et al (2000) and as observed for amitriptyline N-demethylation (Venkatakrishnan et al, 2000). However, Ludden et al (1997) reported a decreased K mu, whereas V max remained unchanged for PHT hydroxylation by human liver microsomes when BSA was added to decrease free fraction.…”
Section: Discussionmentioning
confidence: 99%